Numerical study on performances of small incline angle helical baffle electric heaters with axial separation. (5th November 2017) - Gu, Huaduo; Chen, Yaping; Wu, Jiafeng; Yang, Shifan
Highlights: Axial separation with small incline angle baffles reduces abrasion of holes on tubes. Axial separation scheme has plug flow velocity field similar to normal helical one. Flow and thermal performances of axial separation and normal schemes were simulated. Average h.t.c. or h ·Δ p −1/3 of HM20(10)° is 37.8% or 26.0% higher than segment scheme. Average wall temperature of HM20(10)° is 95.6 K lower than that of segment scheme. Abstract: To minimize the abrasion of sharp-corners of holes of inclined baffles manufactured by 2D laser beam cutting machine on the tubes, the application of axial separation with small inclined angle helical baffles is a simple alternate, which creates greater helix pitch for suitable cross section area. Numerical simulation on the flow and thermal performances were conducted on three axial separation helical baffle electric heaters with equivalent angles 15°, 20° and 25° using 10° inclined baffles, three normal helical baffle ones and two segment baffle ones spanned respectively 200 and 250 mm. Each electric heater comprises 27 U-tubes on equilateral triangle layout with nine one-plus-two units. The secondary flow imposed plug flow pattern and leakage flow were demonstrated for helical schemes. The axial separation helical baffle schemes have obvious merits in the heat transfer coefficient, comprehensive index and the temperature uniformity of the electric heating tubes over those of the segment baffle ones. The average heat transfer coefficient and the comprehensive index ( h ·Δ p −1/3 ) of the modified axial separation helical scheme with equivalent angle 20° using 10° baffles are respectively 37.8% and 26.0% higher while its average tube wall temperature is 95.6 K lower than those of the segment scheme spanned 200 mm.